1934
DOI: 10.1002/cber.19340671124
|View full text |Cite
|
Sign up to set email alerts
|

Über Pregnanol‐(20)‐on‐(3)

Abstract: But e n a n d t , Schmidt : ober Pregnanol-(20) -on-( 3 ) . I893 ungeschmolzen. -d) Der bei c) erhaltene Schmelzfld wurde im Thermostaten bei +24O aufbewahrt. Es setzte eine sehr langsame Krystallisation ein. Diese war nach etwa 5 Tagen beendet. Die Schmelzkurve zeigte einen guten Haltepunkt bei 30-31'. -e) Der SchmelzfluS aus Versuch d) wurde bei etwa 5 O eine Nacht aufbewahrt. Es trat dabei zunachst rasche Krystallisation (Modifikat. + 18O) ein, die Schmelzkurve zeigte einen sehr unscharfen Haltepunkt bei 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1934
1934
1942
1942

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It must be borne in mind that vaginal cornification and vaginal mucification are both characteristic of the action of folliculoids inasmuch as even the typical fol' liculoid substances (estradiol or estrone) cause mucification under certain circumstances as mentioned above. Among the substances examined only pregnenolone (compound 39) and androstenediol (compound 18) and the estrane derivatives (compounds [1][2][3][4][5][6][7][8][9] were definitely proven to cause continuous vaginal cornification in chronic experiments. However, most of the other compounds, even though mainly mucifying in their ac' tion, caused transitory cornification of the vaginal epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be borne in mind that vaginal cornification and vaginal mucification are both characteristic of the action of folliculoids inasmuch as even the typical fol' liculoid substances (estradiol or estrone) cause mucification under certain circumstances as mentioned above. Among the substances examined only pregnenolone (compound 39) and androstenediol (compound 18) and the estrane derivatives (compounds [1][2][3][4][5][6][7][8][9] were definitely proven to cause continuous vaginal cornification in chronic experiments. However, most of the other compounds, even though mainly mucifying in their ac' tion, caused transitory cornification of the vaginal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…8 Metrotropic in immature rat. 9 Produced convulsions. l0 Inactive for guinea pig receptivity; active on rabbit endometrium.…”
mentioning
confidence: 99%
“…The hydroxy com pound was injected in 100 mg. doses into five rats, with negative results. In this case therefore, the effect of reduction of the carbonyl group resembles that observed with progesterone, the biological activity of which is destroyed when one of its keto groups is reduced (Butenandt and Schmidt, 1934). In this case, as in our case, the inhibition of activity cannot be ascribed to an abnormally high degree of specificity, for Klein and Parkes (1936) have recently shown that a certain degree of progestational activity is shown by a male hormone derivative which differs structurally from progesterone to an appreciably greater extent than does its reduction product.…”
mentioning
confidence: 59%
“…Equilenine and other substances with varying degrees of potency were isolated from urine by G ir a r d (1933 (1932). Butenandt (1934) made it also from stigmasterol (a sterol of the soya bean) and established its structure. Androsterone, which is a saturated hydroxyketone, was isolated by Butenandt (1931) and has been prepared from cholesterol by R u zick a (1936).…”
Section: T He G Onadsmentioning
confidence: 99%